Criteria of active sites in nonradical persulfate activation process from integrated experimental and theoretical investigations: boron–nitrogen-co-doped nanocarbon-mediated peroxydisulfate activation as an example. Issue 7 (25th June 2020) - Nie, Chunyang; Dai, Zhenhua; Liu, Wenjie; Duan, Xiaoguang; Wang, Chengyin; Lai, Bo; Ao, Zhimin; Wang, Shaobin; An, Taicheng
Abstract : Reliable criteria for identifying the intrinsic active sites in carbocatalysts to mediate an electron-transfer mechanism in persulfate activation are presented. Abstract : Carbon-catalyzed persulfate activation is a metal-free advanced oxidation process for abating aqueous organic micropollutants. Recently, the electron-transfer mechanism in the activation of peroxydisulfate (PDS) has attracted tremendous interest due to its unknown nonradical reaction pathways. The conventionally used atomic-scale descriptors of adsorption energy ( E ads ), O–O bond length ( l O–O ) and S–O bond length ( l S–O ) cannot accurately reflect the ability of the functionalities of PDS in its activation. In this work, a new descriptor, local electrophilicity index ( ω ), which represents the oxidative capacity of adsorbed S2 O8 2−, was included to identify the intrinsic active sites in carbocatalysts via density functional theory calculations. To verify the reliability of the proposed criteria, the catalytic performances of a series of highly boronated and nitrogenated carbon nanotube/nanosheet composites (BCN-NT/NS) with tailored physicochemical properties were comparatively studied for activating PDS to degrade phenol. By integrating the computational and experimental results, the catalytic activity of BCN-NT/NS was determined to not only be related to the contents of heteroatom dopants (B and N), but also the positions of B and N in the co-doping configurations. This study offers reliable criteria for determining the intrinsic catalytic sites in carbocatalysts for the activation of PDS based on an electron-transfer mechanism, which assists the rational design of nanocarbons as advanced catalysts for metal-free oxidation and water remediation.